Civil Society - Wara, Yusuf Abubakar (IGI Global, 2024)
The massive failures of the nation-states and non-state actors such as intergovernmental organizations to protect the life, property and the environment of the citizens in most part of the world make it necessary for civil society organizations to carry out supplementary crucial roles towards development of humanity. In several part of the world, especially in developing countries, authoritarian rules, abuse of human rights, joblessness, poverty, insecurity and global warming have become rampart thereby making the masses destitute and helpless. Undemocratic rule brethren bad governance where human rights violation, economic and societal crises become the order of the day. In such kinds of situations citizen become powerless and inactive in both local and international decision making at political and economic functions. In order to develop and empower humanity, this chapter highlighted the steps taken by civil societies in advocating and supporting global good governance, rendering entrepreneur services, promoting global peace and security and protecting the environment.